2019
DOI: 10.1371/journal.pcbi.1007053
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming dynamics in tumor spheroids: Insights from a multicellular, multiscale model

Abstract: Mathematical modeling provides the predictive ability to understand the metabolic reprogramming and complex pathways that mediate cancer cells’ proliferation. We present a mathematical model using a multiscale, multicellular approach to simulate avascular tumor growth, applied to pancreatic cancer. The model spans three distinct spatial and temporal scales. At the extracellular level, reaction diffusion equations describe nutrient concentrations over a span of seconds. At the cellular level, a lattice-based en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…Current approaches for multi-cellular system modeling for cancer have been recently reviewed [ 176 ] and give an interesting basis for future analysis of glutathione’s role in these systems. An example of modeling tumor spheroids by combining multiscale and multicellular models was recently presented by Roy and Finley [ 177 ]. The model includes detailed kinetic representation of intracellular metabolism linked within the cluster of tumor cells that simulates tumor spheroid systems.…”
Section: Computer Modeling Of Gsh Metabolismmentioning
confidence: 99%
“…Current approaches for multi-cellular system modeling for cancer have been recently reviewed [ 176 ] and give an interesting basis for future analysis of glutathione’s role in these systems. An example of modeling tumor spheroids by combining multiscale and multicellular models was recently presented by Roy and Finley [ 177 ]. The model includes detailed kinetic representation of intracellular metabolism linked within the cluster of tumor cells that simulates tumor spheroid systems.…”
Section: Computer Modeling Of Gsh Metabolismmentioning
confidence: 99%
“…PCK2 and its co-expressed genes were then functionally examined by performing GO and KEGG enrichment analyses, which showed a strong enrichment in metabolic related biological processes. In tumors, metabolic reprogramming is an important feature, with the metabolism playing an important role in tumor anti-oxidative stress, energy production and biosynthesis [22].Therefore, key metabolic genes may play an important role in regulating metabolic networks and may affect various biological processes associated with tumors. Furthermore, PCK2 overexpression in HCC cell lines was shown to reduce cell proliferation, thus further suggesting that PCK2 may be a key gene that affects HCC occurrence and development.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 proteins might interact with the components of TME and may support tumor growth or cause resistance to the ongoing therapy. A detailed proteomic analysis of host cell (SARS-CoV-2 infected colon carcinoma cell line) after the infection was performed [ 49 ]. The SARS-CoV-2 infection affected several pathways.…”
Section: Impact Of Covid-19 On Lung Cancer: How Tme Support This Infementioning
confidence: 99%
“…This increased utilization of glutamine is supported by viral infections [ 52 ]. SARS-CoV-2 infected colon cancer cells have shown that a set of genes involved in the metabolic pathways get altered by this infection [ 49 ]. Also, the TME is usually hypoxic and nutrient deprived which supports suppressed immune response providing a favorable environment for viral growth.…”
Section: Impact Of Covid-19 On Lung Cancer: How Tme Support This Infementioning
confidence: 99%